Вычислите, предварительно упростив числовое выражение (0,6)^2-0,6+(0,5)^2 ---------------------------- 0,13^2+2×0,13×0,12+0,12^2 СРОЧНО!!!
Вычислите, предварительно упростив числовое выражение
(0,6)^2-0,6+(0,5)^2
----------------------------
0,13^2+2×0,13×0,12+0,12^2
СРОЧНО!!!
Ответ(ы) на вопрос:
числ 0,6²-0,6+0,5² = 0,6²-0,6+0,5² = 0,6·(0,6-1)+0,5²
знамен 0,13²+2·0,12·0,13+0,12² (0,13+0,12)² 0,25²
= числ 0,6·(-0,4)+0,25 = -0,24+0,25 = 0,01 = 100 = 4 = 0,16
знам 0,25² 0,25² 0,0625 625 25
Не нашли ответ?
Похожие вопросы